Take (Bamboo) : Hiroshi Teshigahara, Kishin Shinoyama. - Noguchi, Isamu; Isozaki, Arata; Shinoyama, Kishin (Tokyo : [s.n.], 1990)
Privately Published, 1990. Illustrated (illustrator). First Edition. Tokyo: Privately published by Hiroshi Teshigahara, 1990. Original teal green clamshell box stamped in blind and gilt, housing an accordion style fold out collection of images of Teshigahara's (1927-2001) bamboo installation at Sogetsu Kaikan, all taken over the course of one day. The panorama was created by joining 30 of Shinoyama's images together using the Shinorama method. Laid in is a pamphlet with a brief biography and description of the works of both men, featuring essays by Noguchi Isamu and Isozaki Arata. One of an edition of 800 copies.
Engels & Japans
boek
Keywords: Teshigahara, Hiroshi; Shinoyama, Kishin